VD_FINDINFO Décision / 2011 / 767 vom 16. Dezember 2011 - VD Tribunal cantonal (2011)
RADIATION DU RÔLE, DÉPENS | 93 al. 1 let. c LPA-VD, 94 al. 1 let. c LPA-VD, 241 al. 2 CPC (CH), 241 al. 3 CPC (CH)